ACUTE TOXICITY STUDY OF (Z)-1-BENZHYDRYL-4- CINNAMYLPIPERAZINES IN SWISS ALBINO MICE - Barman, Anaxee; S, Shivaprakash; Diwakar, Latha; GC, REDDY (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: The objective was to study the acute toxicity of (Z)-1-benzhydryl-4-cinnamylpiperazine derivatives (1a-c) using Swiss Albino mice. Methods: The acute oral and dermal toxicity studies were carried out based on OECD guidelines by adopting fixed dosage method (the limit dose is 2000 mg/kg body weight of test animal in case of dermal toxicity and 5000 mg/kg in oral toxicity). Toxicity and mortality rates were studied at intervals of 6 hrs and 14 hrs after administration of test compounds for 14 days. Results: (Z)-1-benzhydryl-4-cinnamyl piperazine derivatives (1a-c) at oral treatment of 5000 mg/kg BW and dermal toxicity study of 2000 mg/kg BW did not show any pronounced toxicity indicating their potential use for therapeutic purposes. Conclusion: All compounds 1a-c did not cause any mortality or changes in general behavior of the test animals at oral treatment of 5000 mg/kg BW indicating no conspicuous toxicity at the highest dose administered. Keywords: (Z)-1-benzhydryl-4-cinnamyl piperazine derivatives, Acute toxicity, Albino mice, Cinnarizine, Flunarizine.